Mechanical properties of styrene butadiene rubber with oil palm trunk fiber as filler - Mohd Hazizul, Hamzah (2010)
Synthetic rubber on the other hand is a rubber which is synthesized chemically. Styrene-butadiene rubber is one of them. The synthetic rubber gives different properties from natural rubber in every aspect. The objectives of this research are to investigate the mechanical properties changes in styrene butadiene rubber (SBR) filled with oil palm trunks as fillers and to check the differences in properties between the amounts of fillers used. The purpose of this research is to investigate the properties of styrene butadiene rubber blending with oil palm trunk fiber as filler. The research is based on experimental lab research. The contribution of oil palm trunk as a filler in rubber compound will decrease the burning activities and reducing environmental issues. Many researches have been done in rubber/natural filler blending in order to improve the properties of rubber with economically. The methods in this research are divided into three sections; mixing, molding, and testing. Mixing required two roll mills as a device blending rubber with filler, accelerator and vulcanizing agent. Molding required hot and cold press molding to form a sheet of product before testing. Testing required a universal testing machine to test the tensile properties of the rubber blend. Two chemical used in this swelling test; kerosene and diesel. The samples were put into two different bottles with kerosene inside one bottle and diesel inside another bottle. The time taken to complete the test was 24 hours – exactly one day. The result from testing showed that increasing amount of fillers will actually decrease the tensile strength, increase the tensile modulus and increase swelling behavior of the rubber blend. As conclusion, most of mechanical properties decrease with increasing of filler content. As recommendation, increasing the filler content might give the better result, and giving more information about capability of styrene butadiene rubber to consume more filler.